(untitled) (NAU Journal of Technology and Vocational Education, 2025)
The study examined enhancing safety culture: investigating intentions, attitudes, and occupational health practices among TVET staff in public universities. To guide the study, two research questions and hypotheses were formulated and tested at 0.05 level of significance. The study adopted a correlational survey research design. The population of the study comprised of all 96 Technology and Vocational Education staff from universities in Anambra state. The entire population was used as sample, because of its manageable size. The instrument used for the collection of data was a structured questionnaire made up of 20 items divided into three clusters measuring the relevant dimensions of planned behaviour, occupational health and safety practices. The instruments were validated by two experts, in technology and vocational education. Data collected from the respondents were analyzed using Pearson Product Moment Correlation Co-efficient, linear regression and bias corrected (BC) bootstrapping regression estimate. The findings revealed among others a very high positive relationship between safety intentions and health, based on the findings, it can be concluded that safety intentions predict health and safety practices, It was recommended that mentorship programmes should be organized by administrators to enable staff learn from experienced colleagues and reinforce positive behaviours, establish well-defined occupational health and safety policies aligned with planned behavior, continuously evaluate the effectiveness of interventions and adjust strategies based on feedback and outcome.